The Effect of Goal-Oriented Physical Exercises on Cognitive Functions of Children with Learning Disorder - Hanieh Ghasemian Moghadam; Hasan Mohamadzadeh (رشد و یادگیری حرکتی ورزشی)
Introduction: The present study aimed to investigate the effect of a course of Taekwondo goal-oriented physical exercises on the cognitive functions of children with learning disorders.Methods: In this quasi-experimental study, which was conducted with a pre-test-post-test control group design, 20 boys with learning disorders were selected from the centers for learning disabilities by referring to special education in Mashhad. In the pre-test stage, the participants' working memory and inhibition were measured by N-back and Stroop tests, respectively. After that, the exercise group participated in the selected Taekwondo exercise program for three 50-minute sessions per week for four weeks. In each session, a set of My Brain cognitive games was used before the implementation of the exercise protocol. In the first 10 minutes of the session, cognitive games were played, then 10 minutes of warming up, 30 minutes of teaching and practicing Taekwondo techniques, and finally 10 minutes of cooling down were conducted. During this period, the control group did their usual activities. Finally, the dependent variables were measured again in the post-test phase. Repeated measures analysis of variance test was used for statistical analysis. Results: Taekwondo goal-oriented physical exercises improved cognitive functions in the Exercise group; All these changes were significant compared to the control group (P<0.05).Conclusion: Taekwondo goal-oriented physical exercises can be effective as an intervention to improve the cognitive functions of this group of children.